Persaingan Harga Saham dalam Cerpen Starbucks Coffee, Suatu Senja Karya A. M. Lilik Agung - Eva Dwi Kurniawan; Indri Widiastuti; Febriana Putrika Adhasari (Universitas Katolik Widya Karya Malang, 2024)
This research aims to describe stock price competition in a literary work. The literary work used in this research is a short story entitled Starbucks Coffee, Suatu Senja by A. M. Lilik Agung. The method used is a qualitative approach using document study techniques. The activities carried out were reading, viewing, interpreting and analyzing the short story Starbucks Coffee, Suatu Senja. The results obtained will be described in sentence form. The research results show that there are two aspects contained in the short story Starbucks Coffee, Suatu Senja namely the social aspect and the investment aspect. The social aspect is described by the existence of rivalry/competition from both parties. Meanwhile, the investment aspect is illustrated by the decline in share prices on the stock exchange.